Bentuk-Bentuk Sapaan dalam Novel the Prince and the Pauper - Lumoindong, Boy (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Klabat, 2023)
Abstract Addressing people is an essential element and unavoidable in every discourse as it marks the beginning of a smooth discourse construction. Every language has its specific terms of address that is largely influenced by various aspects in the speech community. This reasearch is aimed at identifying and describing the terms of address thats are used by the two main figures in the novel written by Mark Twain (Samuel Langhorne Clemens) entitled The Prince And The Pauper. In this research the researcher implemented the descriptive method is his attempt to present in detail his analysis of the research question. The data of this research is collected from many discourse situations uttered by the two main figures in this novel. The data is the reduced and analyzed based on the situastion, status, identity, and ascending generation of the figures according to the the set of rules of terms of address presented by Ervin Tripp. The result of this research shows that the terms of address used in this novel is accordingly based on the set of rules of terms of address by Ervin-Tripp, so the result of this research supports the aforementioned rules. Keywords —Address, Rules, Discourse, Figure, Novel